Answer:
7.21m/s
Step-by-step explanation:
Using the law of conservation of momentum expressed as;
m1u1 + m2u2 = (m1+m2)v
m1 and m2 are the mass of the man and the stone respectively
u1 and u2 are their respective initial velocities
v is their final common velocity
Given
m1 = 96kg
m2 = 75g = 0.075kg
u1 = ?
u2 = 0m/s (initial speed of the stone)
v = 7.2m/s
Substitute into the firmula and get u1
96u1 + 0.075(0) = (96 + 0.075)(7.2)
96u1 = 96.075(7.2)
u1 = 691.74/96
u1 = 7.21m/s
Hence the man acquired a speed of 7.21m/s